The Peep Diaries - Şenol Karadeniz (Türk Kütüphaneciliği)
Hal Niedzviecki who is a Canadian novelist and cultural critic was born in 1971, Canada. He did his undergraduate studies at the University of Toronto and his graduate studies at Bard College. Niedzviecki’s The Peep Diaries explores how contemporary communication technologies and social networks has evolved many people’s life.